Satisfaction with a performance praisal system in Jesselton College : the importance of perceptions of justice and accuracy / Siti Munirah Berhan @ Birhan, Razman Ab Razak and Effmawie Mohd Efendi - Berhan @ Birhan, Siti Munirah; Ab Razak, Razman; Mohd Efendi, Effmawie (2016)
Jesselton College is a private higher learning institution in Kota Kinabalu that stresses on its Human Resource quality to achieve its vision and mission. As such, job satisfaction, of which performance appraisal system are one of the important element, plays an important role. This study was conducted to determine employees' satisfaction on performance appraisal system in Jesselton College, as well as to determine the effect of the employees' perception of justice and accuracy towards their satisfaction with the performance appraisal. 30 respondents were involved in this study utilizing the survey approach. The findings led to a recommendation for improvements to the existing performance appraisal system with a range of suggested implementable initiatives, aiming at improving the employees' satisfaction with the performance appraisal by improving their perception of justice.